High-Level Modeling and Synthesis of Analog Integrated Systems - Martens, Ewout S. J. (Springer, 2017)
Various approaches for finding optimal values for the parameters of analog cells, like op amps, have been investigated since the mid-1980s, and they have made their entrance in commercial applications. However, a larger impact on the performance is expected if tools are developed which operate on a higher abstraction level and consider multiple architectural choices to realize a particular functionality. High-Level Modeling and Synthesis of Analog Integrated Systems examines the opportunities, conditions, problems, solutions and systematic methodologies for this new generation of analog CAD tools.